Mast Cells in the Auditory Periphery of Rodents - Agnieszka J. Szczepek; Tatyana Dudnik; Betül Karayay; Valentina Sergeeva; Heidi Olze; Alina Smorodchenko (Brain Sciences, 2020)
Mast cells (MCs) are densely granulated cells of myeloid origin and are a part of immune and neuroimmune systems. MCs have been detected in the endolymphatic sac of the inner ear and are suggested to regulate allergic hydrops. However, their existence in the cochlea has never been documented. In this work, we show that MCs are present in the cochleae of C57BL/6 mice and Wistar rats, where they localize in the modiolus, spiral ligament, and stria vascularis. The identity of MCs was confirmed in cochlear cryosections and flat preparations using avidin and antibodies against c-Kit/CD117, chymase, tryptase, and FcεRIα. The number of MCs decreased significantly during postnatal development, resulting in only a few MCs present in the flat preparation of the cochlea of a rat. In addition, exposure to 40 µM cisplatin for 24 h led to a significant reduction in cochlear MCs. The presence of MCs in the cochlea may shed new light on postnatal maturation of the auditory periphery and possible involvement in the ototoxicity of cisplatin. Presented data extend the current knowledge about the physiology and pathology of the auditory periphery. Future functional studies should expand and translate this new basic knowledge to clinics.